Enhancing Moral Understanding and Character Development in Higher Education: Insight from Skinner Learning Theory - Dimyati Sajari; Dwirahayu, Gelar; Muhammad Umudee (State Islamic Institute of Madura, 2025)
B.F. Skinner, as a behaviourist, emphasized that Learning is shaped more by observable behaviour than by cognition alone. This study explores the application of Skinner’s theory in moral education, aiming to enhance students’ attitudes and character development. Conducted during the odd semester of the 2022 to 2025 academic year, the research employed a case study involving 154 undergraduate students from the Mathematics Education program at UIN Syarif Hidayatullah Jakarta. Findings indicate that applying Skinner’s principles significantly improved students’ cognitive understanding of moral concepts, as reflected in an average score of 82%. More notably, students demonstrated positive behavioural changes through presentations and individual assignments, including reflective activities that encouraged them to connect moral theory with personal conduct. The novelty of this study lies in extending Skinner’s theory—traditionally applied to cognitive Learning—into the domain of moral education, highlighting its relevance for character formation in higher education. While current instructional practices remain predominantly cognitive, this research advocates for a more balanced approach that integrates behaviour-focused strategies to foster moral development. The findings affirm that Skinner’s theory remains a viable pedagogical framework for cultivating both understanding and ethical behaviour among university students.